Down to the sea with Mr. Magee (Mr. Magee books, 1, 1, 2006)
With enough lunch for three, Mr. Magee and his dog Dee head out to the sea. But what begins as a fun day in the sun turns a bit bumpy when onel playful whale decides to say hello. Soon the crew that once was floating finds themselves flying! How will they get down? Who will come to their rescue? And when will they ever get to eat lunch? Down to the Sea with Mr. Magee is a great read-aloud, sure to provide fits of giggles.

Song for a whale (Delacorte Press, Random House Children's Books, Books on Tape, [Listening Library], 2019)
In the spirit of modern-day classics like Fish in a Tree and Counting by 7s comes the Schneider Family Book Award-winning story of a deaf girl's connection to a whale whose song can't be heard by his species, and the journey she takes to help him. From fixing the class computer to repairing old radios, twelve-year-old Iris is a tech genius. But she's the only deaf person in her school, so people often treat her like she's not very smart. If you've ever felt like no one was listening to you, then you know how hard that can be. When she learns about Blue 55, a real whale who is unable to speak to other whales, Iris understands how he must feel. Then she has an idea: she should invent a way to "sing" to him! But he's three thousand miles away. How will she play her song for him? Full of heart and poignancy, this affecting story by sign language interpreter Lynne Kelly shows how a little determination can make big waves. "Fascinating, brave, and tender...a triumph." --Katherine Applegate, Newbery Award-winning author of The One and Only Ivan

Willa and the whale (Shadow Mountain, Shadow Mountain Publishing, 2020)
When her mother dies, twelve-year-old Willa feels lost and alone except when she connects with things her mom loved about the wonders of the ocean as a marine biologist. While on a whale-watching excursion with her dad, who is trying to cheer her up after Willa is sent to live with him and his new family, Willa is alone on one side of the boat when she sees a humpback whale. Her awe and wonderment about this massive and beautiful creature turns to shock when the whale communicates with her, introducing herself as Meg and exchanging small talk. Willa asks if they can talk again, and Meg tells her that if she goes to the edge of the shore and calls out to her, she'll reply. Whales, after all, are very social creatures and communicate by sounds that can travel for miles, underwater. As their friendship develops, Willa views Meg as a trusted confidant who offers sound advice about dealing with a nemesis at school and trying to figure out why her best friend, Mark, is keeping secrets about his family life--all the kinds of talks her mom would normally have with her. She also learns about how similar whales are to humans in caring deeply for their babies, creating communities called "pods," and even singing. When a blue whale washes up on shore and dies, the townspeople jump into action with opinions about what to do with it. Blue whales are the largest animals known to have ever existed, so there is no simple solution. Some are advocating blowing up the whale, some want to cut it up and drag it out to sea, others say let it rot on the obscure beach. Willa is outraged by what she views as inhumane treatment of the deceased whale and vows to do something about it, which is precisely what her mom would have wanted. She knows this is a problem she can't tackle alone, though, and enlists her friends, family, and the City Council to rescue the body of the whale and donate it to the local university where her mom taught for further study and to display the bones. Feeling good about getting her community to band together in service of science and conservation, Willa returns to the shore to tell Meg about her amazing experience. Her joy is tempered with sadness when Meg tells Willa that it is time for her pod to migrate, but it's okay to say goodbye because they will always be connected in a special way in their hearts because they care about each other and showed it by listening and learning about each other. Willa and the Whale is a poignant story about caring and loss and the deep connections that make us human.

Moby Dick, or, The whale (Mackin classics, ,, 2001)
"As a revelation of human destiny it is too deep even for sorrow", was how D.H. Lawrence characterized MOBY-DICK. Published in the same five-year span as The Scarlet Letter , Walden , and Leaves of Grass , this great adventure of the sea and the life of the soul is the ultimate achievement of that stunning period in American letters.
Loomings , Carpet bag , Spouter Inn , Counterpane , Breakfast , Street , Chapel , Pulpit , Sermon , Bosom friend , Nightgown , Biographical , Wheelbarrow , Nantucket , Chowder , Ship , Ramadan , His mark , Prophet , All astir , Going aboard , Merry Christmas , Lee shore , Advocate , Postscript , Knights and Squires , Knights and squires(cont.) , Ahab , Enter Ahab; to him, Stubb , Pipe , Queen Mab , Cetology , Specksynder , Cabin table , Masthead , Quarterdeck , Sunset , Dusk , First night-watch , Midnight: Forecastle , Moby Dick , Whiteness of the whale , Hark! , Chart , Affidavit , Surmises , Mat-maker , First lowering , Hyena , Ahab's boat and crew; Fedallah , Spirit-spout , Albatross , Gam , Town-Ho's story , Of the monstrous pictures of whales , Of the less erroneous pictures of whales, and the true pictures of whaling scenes , Of whales in paint; in teeth; in wood; in sheetiron; in stone; in mountains; in stars , Brit , Squid , Line , Stubb kills a whale , Dart , Crotch , Stubb's supper , Whale as a dish , Shark massacre , Cutting-in , Blanket , Funeral , Sphinx , Jeroboam's story , Monkey-rope , Stubb and Flask kill a right whale, and then have a talk over him , Sperm whale's head; contrasted view , Right whale's head; contrasted view , Battering-ram , Great Heidelburgh turn , Cistern and buckets , Prairie , Nut , Pequod meets the Virgin , Honour and glory of whaling , Jonah historically regarded , Pitchpoling , Fountain , Tail , Grand armada , Schools and schoolmasters , Fast-fish and loose-fish , Heads or tails , Pequod meets the Rosebud , Ambergris , Castaway , Squeeze of the hand , Cassock , Try-works , Lamp , Stowing down and clearing up , Doubloon , Leg and arm; the Pequod of Nantucket meets the Samuel Enderby of London , Decanter , Bower in the Arsacides , Measurement of the Whale's skeleton , Fossil whale , Does the whale's magnitude diminish? Will he perish? , Ahab's leg , Carpenter , Ahab and the carpenter , Ahab and Starbuck in the cabin , Queequeg in his coffin , Pacific , Blacksmith , Forge , Gilder , Pequod meets the Bachelor , Dying whale , Whale watch , Quadrant , Candles , Deck towards the end of the first night watch , Midnight: The forecastle bulwarks , Midnight aloft; thunder and lightning , Musket , Needle , Log and line , Lifebuoy , Deck , Pequod meets the Rachel , Cabin , Hat , Pequod meets the Delight , Symphony , Chase first day , Chase second day , Chase third day , Epilogue.